2020
DOI: 10.3390/ani10122452
|View full text |Cite
|
Sign up to set email alerts
|

Description of Behavioral Patterns Displayed by a Recently Weaned Cohort of Healthy Dairy Calves

Abstract: Animals display movement patterns that can be used as health indicators. The movement of dairy cattle can be characterized into three distinct cluster types. These are cluster type 1 (resting), cluster type 2 (traveling), and cluster type 3 (searching). This study aimed to analyze the movement patterns of healthy calves and assess the relationship between the variables that constitute the three cluster types. Eleven Holstein calves were fitted with GPS data loggers, which recorded their movement over a two wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…Possibly young calves are less able to do so as they have a smaller stomach, or possibly a frequency of two milk feedings per day is simply too far from the voluntary milk feeding frequency of calves, which seems to be around 7 to 8 feedings per day (Webb et al, 2014), leading the calves to visit the AMFs more frequently. In terms of height of peaks, the height of peaks showed that calves become more and more active across the day, from morning to evening, which is consistent with previous research (Alawneh et al, 2020). The respective height of peaks increased as calves grew older, especially the first and the second peaks between week 8 and 20.…”
Section: Discussionsupporting
confidence: 89%
“…Possibly young calves are less able to do so as they have a smaller stomach, or possibly a frequency of two milk feedings per day is simply too far from the voluntary milk feeding frequency of calves, which seems to be around 7 to 8 feedings per day (Webb et al, 2014), leading the calves to visit the AMFs more frequently. In terms of height of peaks, the height of peaks showed that calves become more and more active across the day, from morning to evening, which is consistent with previous research (Alawneh et al, 2020). The respective height of peaks increased as calves grew older, especially the first and the second peaks between week 8 and 20.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, GPS can also be used inside barns, though there are some limitations regarding the accuracy and high energy consumption compared with alternatives such as video cameras [ 134 ]. Alawneh et al [ 135 ] fitted eleven weaned Holstein calves with GPS data loggers (I got-U GT600, Mobile Action Technology Inc., Taipei, Taiwan) for two weeks during spring in a paddock with 105 × 30 m to describe and analyse movement patterns. Among other observations, Alawneh et al [ 135 ] found that those calves were most active during the afternoon and at night.…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
“…Alawneh et al [ 135 ] fitted eleven weaned Holstein calves with GPS data loggers (I got-U GT600, Mobile Action Technology Inc., Taipei, Taiwan) for two weeks during spring in a paddock with 105 × 30 m to describe and analyse movement patterns. Among other observations, Alawneh et al [ 135 ] found that those calves were most active during the afternoon and at night. Individual or group observations could greatly interest calf welfare evaluations, such as substrate preference and a specific position in the barn or paddock due to thermal conditions.…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
“…GNSS data offer the possibility to monitor animal behaviour, such as foraging, walking and resting, with an accuracy ranging from 57 to 87.5% depending on the circumstances [55][56][57][58][59][60][61][62]. However, the potential of GNSS for behavioural monitoring might benefit from combination with other sensors such as accelerometers [63][64][65][66][67][68][69][70][71][72].…”
Section: Global Navigation Satellite Systems (Gnss)mentioning
confidence: 99%